KARAKTERISTIK MUTU MINYAK ATSIRI DAUN PUCUK MERAH (Syzygium oleana) BERDASARKAN LAMA PENYIMPANAN BAHAN BAKU (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
Essential oil is one of the non-timber forest products which is very beneficial for Indonesia. Syzygium oleana are one of the plants with sufficient potential to know the characteristics of their essential oil quality and are widely distributed in Indonesia. This study aims to determine the quality characteristics of Syzygium oleana leaf essential oil based on the storage time of raw materials by the steam distillation method. This research was conducted in January until February 2018 in Laboratory of Natural Materials Technology and Mineral Chemical Engineering, University of Riau. This experience using completely Random Design Consisting of 3 treatments and 3 repetitions. The yield of essential oil obtained was then observed for color, smell and solubility in ethanol. Long storage of raw materials before refining can increase the amount of essential oil yield, the treatment of storage of raw materials for 48 hours obtained the highest average yield (0.32%) of other treatments. The quality of essential oil from Syzygium oleana follows: The smell of essential oils that have the most distinctive aroma of Syzygium oleana that have been tested by smell test is Syzygium oleana leaves with raw material storage for 48 hours as much as 80% of the panelists said they had a distinctive smell. Visually observed from 3 treatments produced the same color, which is yellow. Essential oil Syzygium oleana has ethanol solubility according to SNI of clove leaf oil with a ratio of 1: 2.Keywords : Characteristics, Essential oils, Syzygium oleana, Storage